2019
DOI: 10.1155/2019/1232146
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Induced SUMOylation of Dynamin-Related Protein 1 Protects the Heart against Ischemia-Reperfusion Injury

Abstract: Background. Zinc plays a role in mitophagy and protects cardiomyocytes from ischemia/reperfusion injury. This study is aimed at investigating whether SUMOylation of Drp1 is involved in the protection of zinc ion on cardiac I/R injury. Methods. Mouse hearts were subjected to 30 minutes of regional ischemia followed by 2 hours of reperfusion (ischemia/reoxygenation (I/R)). Infarct size and apoptosis were assessed. HL-1 cells were subjected to 24 hours of hypoxia and 6 hours of reoxygenation (hypoxia/reoxygenatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Mitophagy is a process involving impaired mitochondrial degradation through lysosomes (Bi et al, 2019;Hsieh et al, 2019;Tian et al, 2019). Mitochondrial fusion is an alteration of mitochondrial morphology through the fusion of two mitochondria (Bian et al, 2019). The protective effects of mitophagy and mitochondrial fusion on cardiovascular FIGURE 5 | Overexpression of Opa1 restores endothelial cell viability and reduces apoptosis after ox-LDL treatment by modulating mitophagy and mitochondrial fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Mitophagy is a process involving impaired mitochondrial degradation through lysosomes (Bi et al, 2019;Hsieh et al, 2019;Tian et al, 2019). Mitochondrial fusion is an alteration of mitochondrial morphology through the fusion of two mitochondria (Bian et al, 2019). The protective effects of mitophagy and mitochondrial fusion on cardiovascular FIGURE 5 | Overexpression of Opa1 restores endothelial cell viability and reduces apoptosis after ox-LDL treatment by modulating mitophagy and mitochondrial fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicated that following I/R injury of the heart, the binding capacity of SUMO1 to Drp1 increased and formed a complex. Zinc promoted mitochondrial fission by increasing the acidification of the complex, thereby eliminating damaged mitochondria and maintaining mitochondrial quality stability, further improving cardiac function [ 43 ]. Evidence revealed that SENP3, an enzyme of deSUMOylation, was associated with apoptosis induction in response to cardiac I/R by affecting Drp1 localization in the mitochondria.…”
Section: The Main Types Of Mitochondrial Ptms In Cardiovascular DImentioning
confidence: 99%
“…The existing clinical therapies do not fully resolve MI/R injury in patients with coronary heart disease. (80).…”
Section: Sumoylation As a Potential Therapeutic Targetmentioning
confidence: 99%